THE RIGHTS OF STUNTED CHILDREN TO HEALTH SERVICES IN DONGGALA DISTRICT - Leli Tibaka; Kartini Malarangan; Nursiah; Rosdian (Tadulako Social Science and Humaniora Journal, 2024)
Children are a gift from God Almighty, whose dignity needs to be protected and their rights guaranteed to grow and develop by their nature. Child health problems in terms of nutrition are one of the priorities of the United Nations. Stunting cases are cases of toddlers who have a length or height that is less than the WHO child growth standards. Article 6 paragraph (1) of the Convention on the Rights of the Child reads "States Parties subscribe to the inherent right of every child to life". The right to health is one of the rights inherent in children and adults. One of the Health Rights for children is the fulfillment of children's nutrition and nutrition, so as not to cause stunting of children. SSGI data from Donggala Regency includes districts that have high stunting cases, with a stunting rate in 2023 of 32.4%. This paper aims to find out and analyze the extent of the convention's implementation on the right of stunting children to health services, the factors that cause the high stunting rate in Donggala Regency, and efforts to provide health services for stunting children.